1999
DOI: 10.1136/mp.52.5.275
|View full text |Cite
|
Sign up to set email alerts
|

The integration of HPV-18 DNA in cervical carcinoma

Abstract: Aims-Little information is available on the patterns of integration into the host chromosomal DNA of cervical carcinomas of human papillomavirus type 18 (HPV-18) DNA, which is associated with up to 20% of these carcinomas. Because integration of the viral genome may be extremely important in the pathogenesis of cervical carcinoma, the aim of this study was to investigate which regions of HPV-18 DNA are integrated into the cellular DNA of cervical carcinomas. Methods-Southern analysis using four subgenomic prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 46 publications
7
77
0
3
Order By: Relevance
“…However, in cervical cancer cells HR-HPV DNA is often integrated into the host genome (13,42,46). Although the integrated genomes retain the E6 and E7 open reading frames (ORFs), the viral E2 ORF is often disrupted, resulting in loss of the E2 protein (2,5). In other cases, the viral E1 ORF is disrupted (26).…”
mentioning
confidence: 99%
“…However, in cervical cancer cells HR-HPV DNA is often integrated into the host genome (13,42,46). Although the integrated genomes retain the E6 and E7 open reading frames (ORFs), the viral E2 ORF is often disrupted, resulting in loss of the E2 protein (2,5). In other cases, the viral E1 ORF is disrupted (26).…”
mentioning
confidence: 99%
“…The frequency of integration of HPV16 was significantly associated with severity of disease (Liu et al, 2008;Szostek et al, 2008). Transcriptional repression of the early promoter by E2 is lost during successful integration, as integrants are truncated forms of the HPV genome lacking full length E2 (Corden et al, 1999).…”
Section: E6 and E7 Expression And Integrationmentioning
confidence: 99%
“…In contrast, high grade CIN lesions have high levels of E6 and E7 mRNA in all layers of the epithelium. The majority of HPV-18-associated carcinomas (Cullen et al, 1991;Pirami et al, 1997;Corden et al, 1999) and most HPV-16-associated carcinomas (Cullen et al, 1991;Pirami et al, 1997;Melsheimer et al, 2004) are found to have HPV genomic integrants within the host genome. This critical step in immortalisation of infected cells allows high and unregulated expression of E6 and E7 protein (Schwarz et al, 1985).…”
Section: E6 and E7 Expression And Integrationmentioning
confidence: 99%
See 2 more Smart Citations